Design Model for the Development of Social Welfare Centres (Puskesos) in Solving Problems and Fulfilling the Development Needs of Puskesos in West Java - Dwi Yuliani; Susilawati; Tuti Kartika (GoAcademica Research & Publishing, 2023)
To achieve prosperity, every citizen has the right to receive the services they need. The government then increases people’s access to these services through the Integrated Service and Referral System (SLRT) at the district/city level and networks with the Social Welfare Center (PUSKESOS) at the village/sub-district level. However, unfortunately, many residents still find it difficult to access the basic services they need. This research then aims to develop an engineering model that can solve and meet the needs of the development of Social Health Centers in West Java. This research will be carried out using a descriptive qualitative approach. The data analysis method used is R&D. Then, the data used in this study came from various research results and interviews. The results of this study then produced a referral service model through Puskesos in Indonesia. This model focuses more on strengthening the capacity of social volunteers as Puskesos officers. Through this model, it is hoped that various problems and needs in developing Puskesos in West Java can be resolved.